ANALISIS KESESUAIAN LAHAN SILVOFISHERY DI INSTALASI SUPM WAIHERU DESA KAIRATU KABUPATEN SERAM BAGIAN BARAT - Karepesina, Musa; Saimima, Nur Asyah; Payapo, Muhammad Zia Ulhaq; Arif, Desilina; Irawati, Irawati (Universitas Pattimura, 2025)
This study aims to collect information on water quality data, specifically physical and chemical parameters, to assess the suitability of the land for fish farming activities in the ponds of the SUPM Waiheru Ambon aquaculture installation in Kairatu Village, Kairatu District, West Seram Regency. Water quality analysis was conducted on several parameters, including physical parameters such as temperature, brightness, salinity, and ammonia. As well as chemical parameters which include DO, pH, TDS, nitrate, nitrite, and phosphate. The results of the field analysis are scored according to the land suitability class (score: 1-3), where this score is then multiplied by the weight, and the results are summed. The sum is then divided by 3 and multiplied by 100%. The final value of this calculation is then matched with the level of the class category to produce a land suitability level. The results of the measurement of water quality parameters on the ponds of SUPM Waiheru Ambon Aquaculture Installation in Kairatu Village for freshwater fish farming activities are still within the normal threshold by established water quality standards. The results of the analysis of the feasibility of SUPM Waiheru Ambon Aquaculture Installation ponds in Kairatu Village are included in the feasible category with the score value of land suitability for cultivation at station 1 of 86.36% (very suitable), station 2 of 80.30% (quite suitable), at station 3 of 83.33% (very suitable) and station 4 of 83.33% (very suitable).